Ingestion Dose Due to Uranium in Water Samples from the Southern Coast of Kerala - Sunil, A.; Ben Byju, S.; Jojo, P.J.; Ramachandran, T.V. (Asian Journal of Chemistry, 2010)
Uranium is the ubiquitous heaviest radioactive element found in all terrestrial substances in different level and is important because of its chemical and radioactive properties. Water comes into contact with minerals under the earth's surface and uranium is transferred into water due to its leaching property. Studies on levels of uranium in water bodies will help to understand the mobilization of the tracer amount of uranium in the ecosystem. Water samples from various water sources distributed around the high background region of south India were collected and analyzed for uranium, using dry fission track registration technique, capable of determining the uranium levels even in sub-ppb (particles per billion) level. It is observed that the concentration of uranium is high in seawater as compared to that in tap water. Present work discusses the methods of measurements and the results obtained in detail. From the measured concentration of uranium in water samples, ingestion dose were calculated for an individual using the dose coefficients